PROGRES PENGAKUAN MASYARAKAT HUKUM ADAT DALAM SISTEM HUKUM DI INDONESIA - Rahma Shartika; Nova Febrina Barus; Rosmalinda Rosmalinda (JOURNAL SAINS STUDENT RESEARCH, 2024)
This study discusses the progress of recognizing customary law communities within Indonesia's legal system. As a country rich in cultural and ethnic diversity, Indonesia has a wide array of customary laws that have existed since ancient times. These customary laws play a significant role in shaping written laws and regulating societal behavior and dispute resolution. The 1945 Constitution of the Republic of Indonesia Article 18B (2) provides a constitutional basis for recognizing and respecting customary law communities and their traditional rights. Although there has been progress in acknowledging and protecting the rights of customary law communities, various challenges remain in implementation and harmonization with positive law. This research employs a normative juridical method, using a statutory and historical approach. The results indicate that customary law has been officially recognized since the Dutch Colonial era, with a clearer recognition of customary law communities' rights emerging post-reform in 1998. In conclusion, recognizing customary law in Indonesia is a crucial step toward creating inclusive legal regulations, respecting cultural diversity, and promoting social justice and sustainable development.